An Institutional Understanding of the Transfer of Knowledge to Policy Processes: The Case of The Southern African Development Community’s Regional And National Vulnerability Assessment Committees. - Landman, Annie Petronella (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.